Comparative Analysis of The Effectiveness of TikTok and Instagram as Marketing Media For Skintific Products - Aryanta, Agnesya Putri; R. Yuniardi Rusdianto (Lavish Opulent Education, 2025)
Social media today functions not only as a channel for interaction between businesses and customers but also serves as a key tool for enhancing brand awareness and driving sales. In Indonesia, Instagram and TikTok hold significant positions in shaping social media consumption behavior. This study aims to compare the effectiveness of these two platforms in the marketing strategy of Skintific, a brand that began operations in Indonesia in early 2022. A comparative quantitative method was employed, collecting data through surveys administered to respondents who had been exposed to Skintific advertisements on both TikTok and Instagram. Statistical parametric analysis was conducted on indicators such as engagement, brand awareness, and purchase intention. The results revealed a significant difference in marketing effectiveness between the two platforms, with TikTok achieving a higher average score compared to Instagram. These findings suggest that TikTok is more effective for Skintific's marketing activities in Indonesia than Instagram.